1995
DOI: 10.1103/physrevb.51.16388
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of the ferroelectric-paraelectric transition in the mixed systemPbZr1x

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…With sixth-order terms and following [140,162], ðb à þ b 0 à Þ\ 0 and b 0 à [ 0 can give the sequence of stability with falling temperature to be cubic-tetragonal-orthorhombicrhombohedral. The strain data confirm that in the vicinity of the MPB, at least, the system is close also to the tricritical limit, ðb à þ b 0 Ã Þ ¼ 0, as expected from the known proximity of the tricritical point [14,15,19,73,106].…”
Section: Appendix: Formal Strain Analysissupporting
confidence: 63%
See 2 more Smart Citations
“…With sixth-order terms and following [140,162], ðb à þ b 0 à Þ\ 0 and b 0 à [ 0 can give the sequence of stability with falling temperature to be cubic-tetragonal-orthorhombicrhombohedral. The strain data confirm that in the vicinity of the MPB, at least, the system is close also to the tricritical limit, ðb à þ b 0 Ã Þ ¼ 0, as expected from the known proximity of the tricritical point [14,15,19,73,106].…”
Section: Appendix: Formal Strain Analysissupporting
confidence: 63%
“…order but close to a tricritical point [14][15][16][17][18][19]. The same transition extends along the PT-PFN binary [20].…”
Section: Phase Transitions and Location Of The Morphotropic Phase Boumentioning
confidence: 97%
See 1 more Smart Citation
“…Later, several studies in the F RL and the F RH structures were performed. [7][8][9] These results indicated that the increase of the spontaneous polarization near the F RL -F RH phase transition is related to the O 3 tilt coupling to cation shifts along ͗111͘ axis, and depends on the composition ͑Ti content͒ and the dopant content. Along with the structural research, other physical properties at the F RL -F RH phase transition have also been investigated.…”
Section: Introductionmentioning
confidence: 68%
“…The experimental results for T*, T C , and ⌬TϭT*ϪT C , corresponding to different niobium contents, are presented in Table I along with the dependence on Ti content. This notation for the extrapolated Curie-Weiss temperature (T C ) and the transition temperature (T*уT C ) is the same as that used in our previously published work 21 but differs from that used by other authors, which is T 0 and T C , respectively, for the Curie temperature and the transition temperature.…”
Section: Methodsmentioning
confidence: 99%